Transport to the Slaughterhouse Affects the Salmonella Shedding and Modifies the Fecal Microbiota of Finishing Pigs - Francesca Romana Massacci; Alessandra Morelli; Lucilla Cucco; Adrien Castinel; Roberta Ortenzi; Silvia Tofani; Giovanni Pezzotti; Jordi Estellé; Marta Paniccià; Chiara Francesca Magistrali (Animals, 2020)
Contaminated pork is a significant source of foodborne Salmonellosis. Pork is contaminated at the slaughterhouse and the intestinal content is the predominant source of Salmonella for carcass contamination. The prevalence of Salmonella-positive pigs increases significantly when the time of transport to the slaughterhouse is longer than two hours. The hypothesis behind this study is that transport to the slaughterhouse increases the load of Salmonella in feces and determines a shift of the fecal microbiota in finishing pigs. Fecal samples were collected in a pig herd positive for Salmonella spp., the day before the transport and at the slaughterhouse. Salmonella loads were estimated by the most probable number (MPN) technique, according to the ISO/TS 6579-2:2012/A1. Moreover, the fecal bacteria composition was assessed by sequencing the V3-V4 hypervariable regions of the 16S rRNA gene. Our study showed that the load of Salmonella increases after transport, confirming that this phase of the production chain is a critical point for the control of Salmonella contamination. A lower richness and an increased beta-diversity characterized the fecal microbiota composition of Salmonella-positive animals after transport. In this stage, a natural Salmonella infection causes a disruption of the fecal microbiota as observed in challenge studies.